Gestión de la empresa integración avícola Oro S.A. parroquia Yaruqui, cantón Quito, provincia de Pichincha, periodo 2024-2028 - Verdezoto Guillin, Lenin Rene (2025)
The main objective of this thesis was the development of a management plan for the company Integración Avícola Oro S.A., located in the Santa Rosa neighborhood, Yaruquí parish, Quito Canton, Pichincha Province, for the period 2024-2028. To achieve this purpose, objectives were set that include making a diagnosis of the current situation, formulating strategies based on analysis of the environment and the internal situation, by proposing a plan that focuses on improving the efficiency of the company. The methodology applied included bibliographic research to support the theoretical aspects and field research that facilitated the collection of precise information within the company. A mixed approach was adopted combining qualitative and quantitative elements. Deductive-inductive research methods were also used. The data collection techniques consisted of surveys directed to employees and interviews with the manager, obtaining valuable information on the needs of the company. Analysis of information gathered from surveys and interviews identified key strengths, such as managerial experience and production capacity, as well as areas for improvement needed to address environmental threats. The conclusions underline the importance of a proactive approach to management, while the recommendations suggest the formation of a multidisciplinary team in charge of carrying out an annual evaluation of the SWOT and PESTEL analyses, in addition to establishing a follow-up report to monitor the progress of the strategic plan